MATEC Web of Conferences - Boyakhchyan, A. (2018)
This article describes combined solar systems with liquid cooling are considered in this article. Solar power systems have long been popular in Europe, but in the Siberian climate these systems were considered to be inappropriate. The paper argues that such installations may be used even in Siberia, and in some regions it will be economically profitable. In this article describe an installation that was assembled to carry out field experiments.